2012
DOI: 10.1118/1.4737890
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gafchromic EBT2 and EBT3 films for clinical photon and proton beams

Abstract: The symmetric configuration of EBT3 presents a major improvement for film handling. EBT3 has similar dosimetric performance as its precursor EBT2 and can, thus, be applied to dose verification in IMRT in the same way. For dose verification in proton therapy the underresponse in the Bragg peak region has to be taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
200
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(213 citation statements)
references
References 26 publications
9
200
0
4
Order By: Relevance
“…Both EBT2 and EBT3 film have been found to be suitable for electron dosimetry in studies by Arjomandy et al (6) and Chan et al, (7) respectively. Reinhardt et al (8) compared the performance of the films and concluded that EBT2 and EBT3 have similar dosimetric performances with the elimination of side orientation dependencies and the reduction of Newton's rings in the case of EBT3.…”
Section: Methodsmentioning
confidence: 99%
“…Both EBT2 and EBT3 film have been found to be suitable for electron dosimetry in studies by Arjomandy et al (6) and Chan et al, (7) respectively. Reinhardt et al (8) compared the performance of the films and concluded that EBT2 and EBT3 have similar dosimetric performances with the elimination of side orientation dependencies and the reduction of Newton's rings in the case of EBT3.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, protons have the added complication of varying LET as a function of depth (or energy) that can strongly impact detector response. Radiochromic film provides high‐resolution measurements, but exhibit a LET dependent response, requires postprocessing, special handling, and supporting data acquisitions for calibration and to control for artifacts 1 , 2 , 3 , 4 , 5 . A promising alternative is provided by diode detectors with small rugged sensitive volumes (SV) that are capable of high resolution and real‐time dose acquisition, and that are now commercially available.…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage of the EBT3 radiochromic film is that it is less sensitive to indoor lighting. Previous studies have investigated characteristics of the EBT3 radiochromic film including its the energy dependence for x‐ray irradiation,3, 4, 5 particle‐type dependence,6 its utility in intensity‐modulated radiotherapy (IMRT) applications,4 its compared with its predecessor (the EBT2 radiochromic film)7, 8 and spectral analysis of EBT3 film for 6‐MV photon beams 9…”
Section: Introductionmentioning
confidence: 99%